Praktik Menulis Fanfiction sebagai Sarana Literasi Digital untuk Pengembangan Keterampilan Menulis Kreatif Mahasiswa Pendidikan Bahasa dan Sastra Indonesia - Andriana, Wahyu Dian; Suyatno; Indrawati, Dianita (Universitas Muhammadiyah Surakarta, 2025)
This study aims to describe the practice of writing fanfiction as a form of digital literacy and its role indeveloping creative writing skills among undergraduate students of Indonesian Language and LiteratureEducation (PBSI) at Surabaya State University. Using a qualitative case study design, the research involved 19 students who have experience in writing fanfiction. Data were collected through an open-ended questionnaire that explored the types of fanfiction chosen, obstacles encountered, and strategies applied to overcome these obstacles. The data were analyzed using thematic analysis. The findings show that Alternative Universe (AU) is the most preferred type of fanfiction because it offers flexibility inexploring narrative possibilities and personal experiences. The main obstacles faced by students includetechnical difficulties in structuring narratives, limited ideas, time management problems, lowmotivation, limited access to relevant references, and challenges in conveying emotions. To addressthese constraints, students employ various strategies such as regular writing practice, referenceexploration, structured time management, and seeking support from online communities and academicenvironments. This study highlights fanfiction writing as a meaningful digital literacy practice that canbe integrated into creative writing pedagogy for prospective Indonesian language teachers.